2002
DOI: 10.2741/a831
|View full text |Cite
|
Sign up to set email alerts
|

T cells and aging january 2002 update

Abstract: Age-related changes in the immune system may contribute to morbidity and mortality due to decreased resistance to infection and, possibly, certain cancers in the aged. Many studies mostly performed in mice, rats and man but also including monkeys and dogs have established that age-associated immune decline is characterized by decreases in both humoral and cellular responses. The former may be largely a result of the latter, because observed changes both in the B cell germline-encoded repertoire and the age-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
127
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 354 publications
(137 citation statements)
references
References 26 publications
(44 reference statements)
10
127
0
Order By: Relevance
“…There was, however, a significant decrease in perforin+ cells, as previously reported (Rukavina et al, 1998). These data are therefore in general agreement with results previously reported in different populations (Pawelec et al, 2002a;Pawelec et al, 2004;Pawelec et al, 2005). In order to examine the general effect of viral infection on T cell subset distribution, we separately analysed these data for young and old individuals, comparing those seropositive for both EBV and CMV with those seronegative.…”
Section: T Cell Subsetssupporting
confidence: 87%
See 3 more Smart Citations
“…There was, however, a significant decrease in perforin+ cells, as previously reported (Rukavina et al, 1998). These data are therefore in general agreement with results previously reported in different populations (Pawelec et al, 2002a;Pawelec et al, 2004;Pawelec et al, 2005). In order to examine the general effect of viral infection on T cell subset distribution, we separately analysed these data for young and old individuals, comparing those seropositive for both EBV and CMV with those seronegative.…”
Section: T Cell Subsetssupporting
confidence: 87%
“…shows the surface phenotypes of the CD8 cells in the young and old donors, clearly delineating significantly lower percentages of CD27+, CD28+ and CD45RA+ cells in the elderly, as expected from previous reports (Pawelec et al, 2002a;Pawelec et al, 2004;Pawelec et al, 2005). Reciprocally, the percentage of CD45RO+ cells was significantly increased in the elderly.…”
Section: T Cell Subsetssupporting
confidence: 85%
See 2 more Smart Citations
“…[5] Moreover, in the aging process, and even in centenarians, there is a redistribution of monocytes, neutrophils, B and T subsets, and a quite normal number of T lymphocytes, even if these cells mostly show a memory phenotype, whereas a progressive reduction of virgin cells is observable, which makes the old individuals unable to respond to antigens not previously encountered. [6] Several studies have largely demonstrated an important role of genetic background in the achievement of advanced age. A group of genes that has often been tested for association with successful aging is that which influences inflammation and immune responses.…”
Section: Introductionmentioning
confidence: 99%